A rare case of coexisting tuberculosis with hydatid disease from North India with review of literature. Issue 9 (7th September 2020) - Verma, Prashant Kumar; Rohilla, Ranjana; Natarajan, Vivekanand; Gupta, Puneet Kumar
Abstract : Coexisting tuberculosis (TB) and hydatid disease in an immunocompetent individual is an extremely rare occurrence. Given the similarities in the clinical manifestations and morbidities of both, specific diagnosis in individuals coinfected with these is difficult. We, hereby present a case of a 17-year-old adolescent man diagnosed to be a coinfection of pulmonary TB with pulmonary and cardiac hydatid disease, with the review of cases having a similar presentation. The coexistence of these infections should be considered in endemic areas. Management can only be done by a multidisciplinary approach including surgical, microbiological, histopathological and radiological facilities. Complete surgical excision of the cyst is the treatment of choice and medical therapy for both aetiologies should be appropriate to achieve cure.